2023
DOI: 10.3390/nu15224722
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extracelluar Vesicles Derived from Akkermansia muciniphila on Intestinal Barrier in Colitis Mice

Ting Zheng,
Haining Hao,
Qiqi Liu
et al.

Abstract: Inflammatory bowel disease (IBD) is a chronic and recurrent disease. It has been observed that the incidence and prevalence of IBD are increasing, which consequently raises the risk of developing colon cancer. Recently, the regulation of the intestinal barrier by probiotics has become an effective treatment for colitis. Akkermansia muciniphila-derived extracellular vesicles (Akk EVs) are nano-vesicles that contain multiple bioactive macromolecules with the potential to modulate the intestinal barrier. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…We also found enriched abundance of Akkermansia muciniphila (phylum Verrucomicrobia ) in the HDN group, Akkermansia aids in the development and preservation of the intestinal mucus layer, improves the functionality of the intestinal barrier, inhibits the proliferation of detrimental bacteria, and diminishes the concentration of intestinal endotoxins, thus protecting intestinal health (Zheng et al, 2023 ). Akkermansia reduces the risk of obesity, diabetes, enteritis, colon cancer and other diseases (Li et al, 2023 ; Zheng et al, 2023 ). However, the abundance of A. muciniphila is increased in experimental animals and humans with CKD (Lakshmanan et al, 2021 ), accompanied by an increase in indoxyl sulfate and p-cresyl sulfate (pCS).…”
Section: Discussionmentioning
confidence: 85%
“…We also found enriched abundance of Akkermansia muciniphila (phylum Verrucomicrobia ) in the HDN group, Akkermansia aids in the development and preservation of the intestinal mucus layer, improves the functionality of the intestinal barrier, inhibits the proliferation of detrimental bacteria, and diminishes the concentration of intestinal endotoxins, thus protecting intestinal health (Zheng et al, 2023 ). Akkermansia reduces the risk of obesity, diabetes, enteritis, colon cancer and other diseases (Li et al, 2023 ; Zheng et al, 2023 ). However, the abundance of A. muciniphila is increased in experimental animals and humans with CKD (Lakshmanan et al, 2021 ), accompanied by an increase in indoxyl sulfate and p-cresyl sulfate (pCS).…”
Section: Discussionmentioning
confidence: 85%
“…EVs derived from the intestinal microbiome can represent ideal mucophilic drug carriers, as they are intrinsically able to pass through the aseptic mucous layer of the colon by different routes, enter the border intestinal epithelial cells, interact with mucosal immune cells and the intestinal vascular system, and promote its wide and systemic spread. Zheng et al demonstrated in a mouse model of colitis that EVs derived from the bacterium Akkermansia muciniphila , a mucophilic member of the gut microbiota, prevent disease symptoms by reducing mucosal damage and increase the expression of MUC2 [ 151 ]. The reparation of mucosal damage on colon tissue was also demonstrated using EVs derived from B. acidifaciens in a colitis mouse model, with a complete restoration of the mucus and gut microbiota balance [ 152 ].…”
Section: Resultsmentioning
confidence: 99%
“…They offer diverse therapeutic alternatives such as anti-infection, anti-inflammation, anti-tumor, anti-aging, and more [ 24 ]. Furthermore, Zheng et al demonstrated the therapeutic potential of BEVs derived from Akkermansia muciniphila in reducing mucosal damage, increasing MUC2 expression, and subsequently improving mucus integrity, leading to a reduction in the intestinal permeability in mice with colitis [ 25 ]. Similarly, BEVs derived from Bifidobacterium acidifaciens were shown to induce the repair of mucosal damage and achieve complete restoration of the mucus and gut microbiota balance in mice with dextran sulfate sodium (DSS)-induced colitis [ 26 ].…”
Section: Introductionmentioning
confidence: 99%